2021
DOI: 10.1038/s41598-021-97449-3
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial calcium uniporter promotes arrhythmias caused by high-fat diet

Abstract: Obesity and diabetes increase the risk of arrhythmia and sudden cardiac death. However, the molecular mechanisms of arrhythmia caused by metabolic abnormalities are not well understood. We hypothesized that mitochondrial dysfunction caused by high fat diet (HFD) promotes ventricular arrhythmia. Based on our previous work showing that saturated fat causes calcium handling abnormalities in cardiomyocytes, we hypothesized that mitochondrial calcium uptake contributes to HFD-induced mitochondrial dysfunction and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…CaMKII-dependent SR Ca 2+ leak is linked to mitochondrial metabolic dysfunction, presumably due to changes in Ca 2+ retention capacity of the mitochondria ( 99 ). Inhibition of extramitochondrial CaMKII protects cardiac mitochondria from Ca 2+ overload, loss of inner membrane potential, increased ROS, and resulting arrhythmia in models of prediabetes or obesity ( 99 , 100 ). CaMKII is also found in mitochondrial fractions ( 34 ) and has been shown to have direct effects on mitochondrial metabolism ( 33 ).…”
Section: Camkii In Physiologymentioning
confidence: 99%
“…CaMKII-dependent SR Ca 2+ leak is linked to mitochondrial metabolic dysfunction, presumably due to changes in Ca 2+ retention capacity of the mitochondria ( 99 ). Inhibition of extramitochondrial CaMKII protects cardiac mitochondria from Ca 2+ overload, loss of inner membrane potential, increased ROS, and resulting arrhythmia in models of prediabetes or obesity ( 99 , 100 ). CaMKII is also found in mitochondrial fractions ( 34 ) and has been shown to have direct effects on mitochondrial metabolism ( 33 ).…”
Section: Camkii In Physiologymentioning
confidence: 99%
“…HFD can reduce Kv1.5, which generates repolarizing currents. Abnormal repolarization appears to play a role in the pathophysiology of arrhythmias after HFD [ 72 ]. In addition, high lipids exacerbate lipid accumulation and alter the cardiac structure and environment, and we showed that HFD altered Drosophila heart structure, HR, HP, DI, and SI.…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII determines mitochondrial stress responses in heart 137 . Excitingly, in studies targeting high‐fat‐mediated arrhythmias, MCU knockout mice on a high‐fat diet did not exhibit activation of CaMKII compared to controls 78 . And this MCU knockout‐mediated CAMKII inhibition protects cardiomyocytes from saturated fatty acid‐induced mitochondrial dysfunction and exempts ventricular tachycardia after a high‐fat diet 78 .…”
Section: Pathological Role Of Mcu Complex In Metabolic Diseasesmentioning
confidence: 98%
“…Excitingly, in studies targeting high‐fat‐mediated arrhythmias, MCU knockout mice on a high‐fat diet did not exhibit activation of CaMKII compared to controls 78 . And this MCU knockout‐mediated CAMKII inhibition protects cardiomyocytes from saturated fatty acid‐induced mitochondrial dysfunction and exempts ventricular tachycardia after a high‐fat diet 78 . Although evidence suggests that MCU‐mediated mitochondrial Ca 2+ homeostasis plays a role in metabolic heart disease, unfortunately, we do not yet fully understand the mechanism, and the relationship between MCU and the development of cardiometabolic disorders would be a valuable research direction in the future.…”
Section: Pathological Role Of Mcu Complex In Metabolic Diseasesmentioning
confidence: 99%